Psychoeducational Implementation to reduce gadget addiction in children due to distance learning during the Covid-19 pandemic - Asti Melani Astari; Sholihatul Amaliya; Annisa Wuri Kartika; Ayu Purnama; Nahdya Hamida; Nabila Novarani (Universitas Muhammadiyah Malang, 2023)
The distance learning process using mobile phone (gadget) and internet is one of the strategies implemented to keep the learning process going even during the covid-19 pandemic. This method increases the use of gadgets and the internet in elementary school students which can caused a gadget addiction. Dependence on these gadgets causes obesity problems, sleep pattern disturbances, decreased brain and eye function, growth and development disorders and even mental problem. Psychoeducation is a strategy that can be applied to reduce gadget addiction. Psychoeducational activities are carried out by providing material for 45 minutes which is adjusted to the tendency of the five senses used in receiving student information with the Primary System instrument. Classes will be divided into two groups, visual and auditory. Evaluation of psychoeducational activities was carried out after three days of psychoeducational activities by measuring the level of student addiction to gadgets with the Smartphone Addiction Scale-Short Version instrument (SAS). Psychoeducational activities have been proven to reduce the level of gadget addiction at school, marked by a decrease in SAS-VS scores after psychoeducation with a p value of 0.001 (0<0.005). The results of the activity show the importance of educational activities to reduce children's gadget addiction. The next suggestion is that parents' participation is also needed to facilitate children to carry out other activities so that children are not dependent on the use of gadgets.